(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
The reversible rat liver arginase at low pH conditions was investigated. It is shown that after 12 h pH 3.6 enzyme inactivation is able to recover its activity at the presence of different factors. Due to hypoxia 2 protein fractions (molecular weight of 55650–71200 Da) were indused, which then were added to the reactivation medium. It is reported that the addition of these fractions leads to reactivation up to 72%. Therefore, it is possible that during our experiments low weight proteins have chaperon-like properties, which assist with folding process.